ANALISIS SKALA EKONOMIS PADA INDUSTRI UKIRAN KAYU DI KABUPATEN BADUNG - Deviansa, I made Indra; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No.4, April 2018 (pp. 617-867), 2018)
The growth of the industrial sector is influenced by the scale of the business or scale of production, the greater the scale of production enterprises tend to use factors of production or high input so the company will grow more rapidly. This paper aims to analyze the influence of labor and capital simultaneously on the wood carving industry in Badung regency, to analyze the effect of labor and capital partially on the wood carving industry in Badung regency, to analyze the economical scale of wood carving industry in Badung regency and to know the nature of industrial production wood carving in Badung regency. The study was conducted in Badung regency, researching wood carving industry with a population of 537 business units with multiple linear regression analysis techniques. Samples were taken as many as 85 at random using the Slovin formula. The result of analysis concluded that labor and capital have significant effect simultaneously to wood carving industry in Badung regency. Labor and capital have a positive effect partially on the wood carving industry in Badung regency. Economical scale of wood carving industry in Badung regency is on decreasing return of scale. The production of wood carving industry in Badung regency is labor intensive.